Legal Protection for Landlords in Housing Development Cooperation Agreement in Kendari City - Meirina Dewi Lubis (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The purpose of the research in this study is to know and analyze the legal protection for landowners in the housing development cooperation agreement in Kendari City. Based on the results of research shows that the legal protection of the fulfillment of the rights of parties, especially landowners if one party makes a performance or breach of promise in a housing development agreement depends on the strength of the housing development agreement made, that is, if made by deed under hand its protection is in accordance with the protection of the Act under hand. Whereas when made by or in the presence of a Notary then by itself the act becomes a Notary deed so that its protective force is in accordance with the protection of the Authentic Act.